Experimental use of mycobacterial antigens in tuberculin skin test on water buffalo - Alessandra Martucciello; Federica Signorelli; Piera Mazzone; Francesco Grandoni; Giovanna Cappelli; Lucia Boccia; Giuseppe Parente; Monica Cagiola; Maria Beatrice Boniotti; Esterina De Carlo; Francesco Napolitano; Giorgio Galiero (Revista Científica)
In Italy, bovine tuberculosis (TB) control in the water buffalo population is mainly carried out using the tuberculin skin test (TST). The test measures the increase in skin thickness 72 hours (h) after the intradermal injection of mycobacterial purified protein derivatives (PPD). The TST can involve the single intradermal test with bovine PPD (PPDB), or the comparative test adding a second injection with avian tuberculin (PPDA), using the couple of PPDs reduces false positives caused by non-tuberculosis mycobacteria. This pilot study aimed to evaluate the potential use of PPDB, PPDA, along with 6 kDa early secretory antigenic target (ESAT-6), 10 kDa culture filtrate protein (CFP-10), and Early Secretory Proteins (ESP) in the TST, in healthy and naturally TB infected buffaloes. Twenty-one buffaloes, gamma-interferon (IFN-γ) test positive, from a TB-out-break herd and 11 buffaloes from a TB-free herd were selected. All subjects were also submitted to the IFN-γ test using the same antigens (Ag) as the TST to verify the cellular response in vitro and to exclude anaergic animals that did not respond to in vitro stimulation with the mitogen. The TST was performed according to the TB Italian National eradication program, and to Reg. EU 2020/689. Eight intradermal injection sites were used on each animal shoulder (4 on the right and 4 on the left side). Three concentrations of the ESAT6-CFP10 protein cocktail (10, 20 and 30 μg) and two of ESP (50 and 100 μg) were inoculated. PPDB and PPDA were always included in the TST, along with PBS as negative control. Skin reactions were measured with calipers before the test and every 24 h for 4 days. The TST was considered positive in animals with an increase in skin thickness between post and pre-dermal test readings of > 4 mm, doubtful if between 2 and 4 mm, negative <2 mm. Negative subjects also exhibited a skin response to PPDB at 24 and 48 h, but it became completely negative at 72 h, the prescribed reading time. In the positive buffaloes, the kinetics of skin responses showed that the strongest response was to PPDB at 24h, with some subjects becoming doubtful at 72 and 96 h. A peak response was observed at 48 hours to PPDA and to 20 μg of the ESAT6-CFP10 protein cocktail, followed by a decrease. The response to ESP-100 μg remained high at 24 and 48 h and then decreased, remaining positive at 72 h. ESP showed the best performance with higher reactivity in positive animals and no reactivity in negative animals at 72 h. Therefore,  ESP could be an excellent candidate for further extensive studies in the buffalo species to improve TST Sensitivity and Specificity.